Event-based reference tracking control of discrete-time nonlinear systems via delta operator method. Issue 17 (November 2019) - Liu, Rongjun; Wu, Junfeng; Wang, Dan
Abstract: This paper investigates the event-based tracking control for delta-sampling systems with a reference model. Takagi–Sugeno (T–S) fuzzy model is used to approximate the nonlinearity. The delta operator is used to implement the discrete-time system. The event trigger is adopted for saving the network resources and the controller forces, and its detection period is designed with the same period of the delta-sampling period. Since the measurement is delayed from the sensor to the event-trigger, the methodology of time-delay systems, called the scaled small gain theorem, is applied for the system stability analysis. The reference output tracking controller is designed to ensure the stability of the resulting system in H ∞ sense. The optimization conditions of the desired H ∞ event-based tracking controller are synthesized, and the simulation example validates its effectiveness finally.